The standard, intervention measures and health risk for high water iodine areas. - Peng Liu (Public Library of Science (PLoS), 2014)
Our study aims to clarify the population nutrient status in locations with different levels of iodine in the water in China; to choose effective measurements of water improvement(finding other drinking water source of iodine not excess) or non-iodised salt supply or combinations thereof; to classify the areas of elevated water iodine levels and the areas with endemic goiter; and to evaluate the risk factors of water iodine excess on pregnant women, lactating women and the overall population of women. From Henan, Hebei, Shandong and Shanxi province of China, for each of 50 ∼ 99 µg/L, 100 ∼ 149 µg/L, 150 ∼ 299 µg/L, and ≥ 300 µg/L water iodine level, three villages were selected respectively. Students of 6-12 years old and pregnant were sampled from villages of each water-iodine level of each province, excluded iodized salt consumer. Then the children's goiter volume, the children and pregnant's urinary iodine and water iodine were tested. In addition, blood samples were collected from pregnant women, lactating women and other women of reproductive age for each water iodine level in the Shanxi Province for thyroid function tests. These indicators should be matched for each person. When the water iodine exceeds 100 µg/L; the iodine nutrient of children are iodine excessive, and are adequate or more than adequate for the pregnant women. It is reasonable to define elevated water iodine areas as locations where the water iodine levels exceed 100 µg/L. The supply of non-iodised salt alone cannot ensure adequate iodine nutrition of the residents, and water improvement must be adopted, as well. Iodine excess increases the risk of certain thyroid diseases in women from one- to eightfold.